Solving DSGE Portfolio Choice Models with Asymmetric Countries - Grzegorz Dlugoszek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper combines the bifurcation theory and the nonlinear moving average approximation to solve asymmetric DSGE models with portfolio choice. Contrary to existing local solution techniques, the proposed method captures the direct effect of risk on agents' portfolios. The risk-adjusted net and gross asset positions are shown to lie close to the ergodic mean of the global solution. Hence, the method is able to account for asymmetries in the model, which improves accuracy of the approximation.
Keywords: E44; F41; G11; 330